Ingrams - a neuropsychological explanation for why people search - Bailey, Peter; Craswell, Nick (Proceedings of the 39th Annual ACM SIGIR Conference (SIGIR 2016), 2016)
Why do people start a search? Why do they stop? Why do they do what they do in-between? Our goal in this paper is to provide a simple yet general explanation for these acts that has its basis in neuropsychology and observed user behavior. We coin the term “ingram”, as an information counterpart to Richard Semon's “engram” or "memory trace". People search to create ingrams. People stop searching because they have created sufficient ingrams, or given up. We describe these acts through a pair of user models and use it to explain various user behaviors in search activity. Understanding people’s search acts in terms of ingrams may help us predict or model the interaction of people’s information needs, the queries they issue, and the information they consume. If we could observe certain decision-making acts within these activities, we might also gain new insight into the relationships between textual information and knowledge representation.